Estudo de compósitos formados a partir de nanopartículas de fluoreto de lantânio - Secco, Henrique de Lima [UNIFESP] (2015)
The combination of materials to form hybrids with unique properties, different from those of the isolated components, is a strategy used to prepare functional materials with improved properties aiming to allow their application in specific fields. Lanthanum fluoride is one of the rare earth ionic compounds most extensively studied nowadays, mainly due to its high ionic conductivity, which makes it attractive for sensors applications, also due to the easy doping of its structure with other rare earth elements, because of the similarity between those elements. This strategy is commonly used to obtain luminescent particles, which may be useful to the manufacturing of electronic devices? displays and biological markers, for instance. In this work, nanoparticles of lanthanum fluoride, undoped and doped with cerium and europium, were synthesized through the co-precipitation method in aqueous solution. The dynamic light scattering analyses and the zeta potential showed that the dispersions present sizes within the nanoscale and good stability. The doping by substitution of the lanthanum by other rare earth elements resulted in smaller particle sizes; and that fact is in accordance with the smaller crystallite sizes calculated for the doped samples. Aiming the formation of solid state films, composites of nanoparticles in an elastomeric matrix, the nitrile rubber (NBR), were prepared. Luminescent films were prepared through the casting and spin coating techniques, based on LaF3 doped with europium and cerium, the films presented characteristic emissions in the violet (392 nm) and orange (592 nm) regions, respectively. The thermal analysis of the composites did not show a significant gain of stability when compared to the nitrile rubber alone. The scanning electron microscopy results indicate different sizes and dispersion of the nanoparticles in the polymeric matrix for each technique of film formation; these differences may result in different optical properties of the composites.